Does a woodpecker use a hammer? - Ziefert, Harriet (Ziefert, Harriet. Think about--., 2014)
"This title in the Think About... series explores and explains that while some animals do indeed use tools, only people have developed things that make it possible to do things that their bodies cannot."--